Digital Transformation in Tourism Destination Promotion: A Case Study on Tourism Actors in Yogyakarta - Laksana, Medika Oga (Politeknik Siber Cerdika Internasional, 2025)
This study aims to examine the application of digital transformation in the promotion of tourist destinations in Yogyakarta, focusing on tourism actors who use digital technology in their marketing strategies. The approach used is qualitative with a case study design. Data were collected through semi-structured interviews with hotel managers, travel agents, restaurants, and tourist attraction managers; questionnaires distributed to employees; and observation of the digital promotion practices implemented. The results showed that the use of social media and online booking platforms is the most common among hotel managers and travel agents, while restaurants and tourist attraction managers still underutilize digital platforms. The main obstacles faced are limited human resources skilled in digital technology and high costs for advertising on digital platforms. The practical implication of this study is the need for more intensive training and diversification of the use of digital platforms by tourism actors in Yogyakarta to improve the competitiveness of these tourist destinations.